Effects of orally-bioavailable short-acting kappa opioid receptor-selective antagonist LY2456302 on nicotine withdrawal in mice. (October 2015) - Jackson, Kia J.; Jackson, Asti; Carroll, F. Ivy; Damaj, M. Imad
Abstract: Kappa opioid receptor (KOR) signaling has been implicated in mediating behavioral and biochemical effects associated with drug dependence. The most commonly used KOR antagonists, norbinaltorphimine (norBNI) and (3R)-7-Hydroxy-N{(1S)-1-{[(3R, 4R)-4-(3-hydroxyphenyl)-3, 4-dimethyl-1-piperidinyl]methyl}-2-methylpropyl}-1, 2, 3, 4-tetrahydro-3-isoquinoline-carboxamide (JDTic), have provided a wealth of information in this area; however, the delayed onset and long-lasting effects of these antagonists complicate experimental design and interpretation of results, and make them less than ideal for clinical studies. Initial studies with the recently developed KOR antagonist, LY2456302, show that the compound is a short acting, high-affinity, selective KOR antagonist with therapeutic potential for mood disorders and ethanol use in animal models, and is well tolerated in humans. The goal of the current study was to evaluate the effectiveness of LY2456302 in alleviating the nicotine withdrawal syndrome in mice. Mice were chronically treated with nicotine for 14 days and physical and affective nicotine withdrawal signs were measured using a spontaneous nicotine withdrawal model and conditioned place aversion (CPA) following pre-treatment with LY2456302, administered orally. Vehicle treated nicotine withdrawn mice displayed significant anxiety-related behavior, somatic signs, hyperalgesia, and CPA. Similar to previous studies with norBNI and JDTic, LY2456302 alleviated the nicotine withdrawal syndrome, as evidenced by decreased expression of nicotine withdrawal induced anxiety-related behavior, somatic signs, and CPA, and increased hotplate latency in nicotine withdrawn mice following pre-treatment. Given the current results, and with its favorable pharmacokinetic and pharmacodynamic profile, LY2456302 may be a useful therapeutic agent for treatment of multiple aspects of the nicotine withdrawal syndrome. Highlights: Kappa opioid receptors, in part, mediate mood and substance use disorders. A new kappa opioid receptor antagonist, LY2456302, may have therapeutic potential. LY2456302 was evaluated for potential to alleviate nicotine withdrawal in mice. LY2456302 reduced expression of physical and affective nicotine withdrawal in mice. Findings suggest that LY2456302 may be efficacious across multiple drugs of abuse.